Patrimonial responsibility of public servants in Nicaragua - Morales Márquez, Odair Marcelo (Scientific journal of social studies, 2022)
The principle of patrimonial responsibility demands that individuals may be compensated by the Public Administration when their rights, assets and interests are injured by administra-tive activity, but the Public Administration also has the right and the obligation to demand from the responsible public servant, the compensation of what the administrative body has disbursed as compensation. This article addresses the patrimonial responsibility of the public servant and the necessary regulation in the Nicaraguan legal system of theoretical and legal constructions that justify the patrimonial responsibility of public servants from the point of view of Administrative Law, through the consideration of theories such as: theory of failure or lack of service, the theory of separation of responsibilities and the theory of shared respon-sibility, among others. This article aims to provide the theoretical and legal foundations, aid-ed by the Comparative Law of countries such as Spain, Colombia and Costa Rica, capable of providing the necessary support for a future implementation of the patrimonial responsibility of public servants and thus increase administrative efficiency and guarantees a good Public Administration. This research uses a deductive analysis method, in the review and synthesis of national and foreign legislation and doctrine on issues of patrimonial responsibility of public servants.
Keywords: Administrative Law; Public server; patrimonial responsibility; liability regimes; repair